Recombinant phage endolysin as antibiofilm agent against staphylococcus aureus and pseudomonas aeruginosa - Yeong, Zi Hui (2024)
The rising number of antimicrobial-resistant (AMR) bacteria is a major global threat. The ESKAPE pathogens, Staphylococcus aureus and Pseudomonas aeruginosa commonly cause biofilm-associated infections. Biofilm formation further enhances antibiotic resistance, compromising conventional therapies. This triggers an urgent search for alternative therapies to combat biofilms, such as phage endolysin. The ability of phage endolysins to cut as anti-bacterial agents was reported in previous studies. Thus, different recombinant endolysins have been produced and investigated for their ability to control pathogens. Likewise, in this study, the endolysin gene, which originated from a novel phage (Escherichia phage KW1E_UTAR), has been cloned and expressed as recombinant endolysin. The recombinant endolysin was shown in a previous study to exhibit an antibacterial effect against S. aureus and P. aeruginosa. However, its antibiofilm activity has not been investigated. Therefore, in this study, both the inhibitory and eradication effect of this recombinant endolysin was determined. Firstly, the S. aureus and P. aeruginosa biofilm formation was optimized. Results showed that both bacteria were strong biofilm producers when cultivated in TSB supplemented with 1.0% (v/v) glucose with an initial and incubated at 37℃. bacterial titer of 108 CFU/mL and incubated at 37℃. Subsequently, the antibiofilm effects of the recombinant endolysins were investigated. The results showed that the minimum 50% biofilm inhibition concentrations (MBIC50) against S. aureus and P. aeruginosa were 1.95 – 7.81 μg/mL and 0.98 μg/mL, respectively. However, MBIC90 for both bacteria was not achieved in this study. On the other hand, the minimum 50% biofilm eradication concentrations (MBEC50) against S. aureus and P. aeruginosa were 15.63 – 31.25 μg/mL and 1.95 μg/mL, respectively. Meanwhile, only MBEC90 against P. aeruginosa was determined at 3.91 – 15.63 μg/mL. Therefore, the present study suggests that the recombinant endolysin can be further explored as an antibiofilm agent clinically isolated S. aureus and P. aeruginosa.